Love of Money, Religiosity and Financial Attitude: Internal Factors of Online Loan Decision - Fitriana, S.E., M.Sc., Vita Elisa; Mapuasari, Supeni Anggraeni; Oktapriana, Chita (JAAF (Journal of Applied Accounting and Finance), 2025)
The increasing trend of micro credit disbursement in the post-pandemic can be interpreted as positive signal for credit development in Indonesia, however, it also creates unfavorable issue for the banking industry. Online loans, have emerged as a community alternative, notwithstanding their limited share of credit distribution. The benefits of online loans are the public's ease of access and the streamlining of the application process. The purpose of this study is to determine which elements can be the primary motivators for someone to apply for a loan online. This study collected data from 133 respondents and analyzed by the structural equation modeling. The statistical results reveal that the love of money and religiosity had a positive effect on financial attitude. But, for the direct effect toward online loan, none of love of money, religiosity or financial attitude significantly influence it. It implies that internal factor which coming from inside of individual is unable to explain their decision result.